2017
DOI: 10.1364/josab.34.001206
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution nonlinear optical spectroscopy of InGaN quantum dots in GaN nanowires

Abstract: High resolution coherent nonlinear optical spectroscopy of an ensemble of red-emitting InGaN quantum dots in GaN nanowires is reported. The data show a pronounced atom-like interaction between resonant laser fields and quantum dot excitons at low temperature that is difficult to observe in the linear absorption spectrum due to inhomogeneous broadening from indium fluctuation effects. We find that the nonlinear signal persists strongly at room temperature. The robust atom-like room temperature response indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…1b) shows a series of resonances that are peaked in amplitude around 2.05 eV and slowly roll off as a function of energy. Similar results from previous studies have been observed [20,26], where the resonant structures in the degenerate nonlinear absorption spectrum were assigned to exciton transitions. Here we attribute the resonances to quantum-confined exciton states from different sized DINWs within the ensemble, an assignment that will be further validated shortly.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…1b) shows a series of resonances that are peaked in amplitude around 2.05 eV and slowly roll off as a function of energy. Similar results from previous studies have been observed [20,26], where the resonant structures in the degenerate nonlinear absorption spectrum were assigned to exciton transitions. Here we attribute the resonances to quantum-confined exciton states from different sized DINWs within the ensemble, an assignment that will be further validated shortly.…”
supporting
confidence: 91%
“…A negative dT/T offset has been observed in previous nonlinear spectroscopy studies of self-assembled DINW samples [20]. The origin of the negative offset, which can be observed in degenerate CPP spectra as well, is still under investigation, however it may be an effect related to bandgap renormalization or screening [20,28,29]. A zoomed-in view of the non-degenerate CPP spectrum for a fixed probe near 1.95 eV is shown in Fig.…”
mentioning
confidence: 60%
See 2 more Smart Citations